Soil organic carbon stocks under different land uses in Chure region of Makawanpur district, Nepal (SAARC Journal of Agriculture, 2019)
Soil C sequestration through enhanced land use is a good strategy to mitigate the increasing concentration of atmospheric CO2. A study was conducted in Chhatiwan VDC of Makawanpur District to compare soil organic carbon (SOC) stocks of four main land use types such as forest, degraded forest, Khet and Bari land. Stratified random sampling method was used for collecting soil samples. Organic carbon content was determined by Walkley and Black method. Total SOC stock of different types of land followed the order: as Forest (110.0 t ha-1) > Bari (96.5 t ha-1) > Khet (86.8 t ha-1) > Degraded land (72.0 t ha-1). The SOC% declined with soil depths. The SOC% at 0–20 cm depth was highest (1.26 %) that recorded in the forest soils and lowest (0.37%) at 80- 100cm depth in degraded forest land. Thus, the SOC stock varied with land use systems and soil depths. The study suggests a need for appropriate land use strategy and sustainable soil management practices to improve SOC stock.SAARC J. Agri., 16(2): 13-23 (2018)